2021
DOI: 10.1101/2021.02.26.433086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bortezomib inhibits lung fibrosis and fibroblast activation without proteasome inhibition

Abstract: The FDA-approved proteasomal inhibitor bortezomib (BTZ) has attracted interest for its potential anti-fibrotic actions. However, neither its in vivo efficacy in lung fibrosis nor its dependence on proteasome inhibition has been conclusively defined. Herein, we identify that therapeutic administration of BTZ in a mouse model of pulmonary fibrosis diminished the severity of fibrosis without reducing proteasome activity in the lung. Under conditions designed to mimic this lack of proteasome inhibition in vitro, i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(96 reference statements)
1
2
0
Order By: Relevance
“…Bortezomib has previously been shown to significantly reduce lung fibrosis in Blm treated mice in two other studies, although it was suggested its effects were through inhibition of transforming growth factor beta signalling (56) or by modulating fibroblast function independent of proteasome inhibition (57). In this study we confirmed that bortezomib reduced lung fibrosis in Blm treated mice but also showed almost complete depletion of PCs in bortezomib treated lung tissue.…”
Section: Discussionsupporting
confidence: 82%
“…Bortezomib has previously been shown to significantly reduce lung fibrosis in Blm treated mice in two other studies, although it was suggested its effects were through inhibition of transforming growth factor beta signalling (56) or by modulating fibroblast function independent of proteasome inhibition (57). In this study we confirmed that bortezomib reduced lung fibrosis in Blm treated mice but also showed almost complete depletion of PCs in bortezomib treated lung tissue.…”
Section: Discussionsupporting
confidence: 82%
“…Several groups have sought to target degradative mechanisms in hepatic and extrahepatic disease through inhibiting the proteosome or autophagy. Bortezomib, a proteosome inhibitor used to treat Multiple Myeloma, reduces liver fibrosis in cholestatic mouse models (MDR2 −/− Bile duct ligation), as well as renal and lung fibrosis in other mouse models (Anan et al, 2006a;Jalan-Sakrikar et al, 2019;Zhou et al, 2019;Penke et al, 2021). The mechanisms associated with the fibrosis reduction differ, with focus on EZH2, TGFβ signaling, or limiting fibroblast activation, but the antifibrotic results were similar.…”
Section: Targeting Protein Degradation In Liver Fibrosismentioning
confidence: 99%
“…Egyptian Journal of Cell and Tissue Research (EJCTR), Volume 2, Issue 1, January, 2024 ___________________________________________________________________________ It was hypothesized that in idiopathic pulmonary fibrosis (IPF), chronic and repetitive alveolar epithelial cell injury occurs with subsequent release of various cytokines as transforming growth factor beta (TGFβ), platelet-derived growth factor (PDGF), fibroblast growth factor (FGR) and vascular endothelial growth factor (VEGF) (18) . TGFβ was clarified to be the main contributor of disease progression (19) .…”
Section: Groupsmentioning
confidence: 99%